Aplikasi Kompos Limbah Sampah Pasar dengan Bioaktivator Larutan Keong Mas dan Trichoderma. Sp terhadap Tanah Bekas Tambang Batu Bara dengan Tanaman Uji Padi Gogo - roro kesumaningwati; Nurul Puspita Sari Puspita Sari; Safryan William Purba (Jurnal Agroekoteknologi Tropika Lembab, 2019)
East Kalimantan has a fairly extensive ex-coal mining area. Continuous mining activities cause severe land damage with a dramatically reduced nutrient. The application of organic farming can be one of the solutions to improve ex-mining land. One of the plants that can be applied is Situ Bagendit Rice. Rice Bagendit varieties are dry land rice which is resistant to pests and blast disease. The use of market waste, MOL golden snail, and Trichoderma. Sp as organic material can increase productivity in Bagendit rice plants there and be able to repair damage to ex-coal mine land. The aim of this study was to compare market waste, MOL golden snail and Trichoderma sp to Bagendite rice plant growth. This study used the RAL method (Completely Randomized Design) with 9 treatments and 3 replications. B0 control (soil without additives), B1 compost market waste and Trichoderma sp with a dose of 100 g/polybag, B2 market waste waste compost and MOL golden snail with a dose of 100 g/polybag, B3 compost market waste and Trichoderma sp with 200 g/polybag, B4 market waste compost and MOL golden snail with a dose of 200 g/polybag, B5 market waste compost and Trichoderma sp with a dose of 300 g/polybag, B6 market waste compost and MOL golden snail with a dose of 300 g/polybag, B7 market waste compost and Trichoderma sp with a dose of 400 g/polybag, B8 market waste compost and MOL golden snail with a dose of 400 g/polybag. The results showed that Trichoderma sp market waste compost fertilizer and golden snail market MOL waste compost each had a significant effect on the productivity of bagendite rice plants. In addition, MOL market golden snail waste compost with the best dosage of 400 g/polybag is able to produce harvested dry grain production of around 2.8 tons/ha.